PEMILIHAN KAPASITAS BATERAI PENYIMPAN ENERGI LISTRIK DARI ENERGI SURYA - Irawan Bambang; Hadi Samsul; Darsin Mahros; Fatkhur Rohman (ROTOR, 2018)
This paper is concern on the using of some solar batteries for storing the energy from the solar panel. The battery used is a 100 WP solar cell with the appliances. Research was carried out in an open air with real condition without treatment for two months continuously during hot dry season in Malang city, Indonesia. It is concluded that emerged energy from the solar panel was 550 WH or equal to 12 V of 45 AH. During the electric charging from solar panel to the battery, the flowing current vary between 2 A to 6 A. The battery charging only started after 7 am when the voltage was above 12 V. For the solar panel 100 WP to use battery with the storage capacity above 40 AH. Keywords: battery, solar panel, energy